Autism Spectrum Disorder: Latest Advances in Treatment - Szpernalowska, Anna; Matshaba, Vimbisoyashe Ivy; Mrugała, Karolina; Choinka, Martyna; Kalisiak, Jakub; Mataczyńska, Anna; Paprocki, Michał (Quality in Sport, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition marked by deficits in social communication and the presence of restricted, repetitive behaviours. Despite the global prevalence of ASD, its diagnosis and treatment remain challenging due to the absence of specific biomarkers and the heterogeneity of symptoms. ASD is incurable and current management options aim to minimize the symptoms and maximize the patients’ ability to function. There is no one standardized treatment for ASD at present, recommended medical interventions involve various therapies which include cognitive behavioral therapy alongside additional personalized pharmacological symptomatic treatments. New approach for ASD management includes sensory integration therapy (SIT) as well as dietary interventions, like gluten-free, casein-free and ketogenic diets. Other innovative treatment strategies are targeted at gut microbiome and include probiotic treatment and fecal microbiota transplant. In this review possible genetic variants associated with ASD are discussed as well as their influence on the manifestation and management of clinical symptoms. For a better understanding on how genetic variables impact drug effectiveness in individuals and the importance of pharmacogenetics in ASD. This paper aims to explore the available and possible treatment options as well the genetic components associated with ASD. In summary, this paper reviews the current and emerging treatment options for ASD.